Vems behov, trygghet och säkerhet ska vi bedöma som tyngst? En studie om registerkontroller - Irmiyahou Bjärnsten,Hanna; Hjalmarsson,Malou (2025)
The current legislative framework regarding criminal record checks in Swedish municipalities can be perceived as lacking and may lead to violations of privacy and exclusions of formerly incarcerated individuals. Criminal record checks can, however, help employers make hiring decisions to ensure safety for elders and children. In light of this dilemma, the aim of this research was to examine the legal and normative tensions between employers’ rights to ensure safety within Swedish municipal services and individuals’ rights to privacy and a fair chance to employment after incarceration. This tension was researched through DS 2024:24, a governmental inquiry proposing an expanded use of criminal record checks and suspension registers in municipal recruitment. The research was made through ten qualitative interviews with municipal employers, legal professionals, government agency employees, and individuals helping formerly incarcerated individuals reintegrate in the labor market. Analyzing the findings through the lens of street-level bureaucracy theories, the study aimed to develop a more understanding and nuanced perspective of how the law and social norms interact. The results revealed that employers apply discretion when using criminal record checks in recruitment and often prioritize risks over offering employment to formerly incarcerated individuals. This dynamic demonstrated a tension between the formal legal rights and social norms, where the need to maintain safety for vulnerable groups can override rehabilitative intentions. The findings also revealed an uncertainty regarding responsibilities between state regulations and employer practices, with expressed desires for clearer guidance to support fair and consistent hiring decisions.
Keywords: Arbetsgivare; gräsrotsbyråkrati; registerkontroller; tidigare fängelsedömda